Centering community-based knowledge in food security response and climate resilience in southern Madagascar - Zambiazzi, Emily; Carr, Elizabeth; Mahazotahy, Sylvain; Mahafake, Charles; Dickey, Chris (Frontiers in Sustainable Food Systems, 2023)
Objective Increasingly unpredictable shifts in climate are triggering public health crises globally. Southern Madagascar is particularly vulnerable to climate impacts, despite contributing to only 0.2% of global emissions. Though endemic in Madagascar, climate impacts such as below average rainfall have increased the severity of droughts, putting over half of the population in southern regions at risk of being food insecure in 2022. The following review examines: How can interventions surrounding the current food emergency in southern Madagascar center community-based knowledge in their strategies? Through a social-ecological approach, this review aims to holistically discuss the complexity of the climate and food crises in this region, which is a topic that has not been widely covered in published review articles thus far. Methods We took a comprehensive and social-ecological approach by analyzing research pertaining to the impacts of colonial history, politics, economy, and culture on the current climate, ecology, and food systems of southern Madagascar. Main findings Many current strategies to mitigate climate impacts and food security fail to incorporate community-based knowledge, leading to inequitable and ineffective interventions. Researchers who prioritize historical and cultural context illustrate how local knowledge may serve as a protective factor against climate impacts. Conclusions As climate shifts exacerbate public health crises, aid organizations must center community perspectives in their interventions to foster equitable and sustainable outcomes.